Muzeum wielkich idei - Gaskell, Ivan (Zbiór Wiadomości do Antropologii Muzealnej, 2019)
Although museums of all kinds continue to proliferate, they have lost the capacity to generate big ideas that characterize epistemic shifts, such as evolution, the labour theory of value, or relativity. The have become echo chambers for ideas proposed elsewhere. The development of Tangible Turn in scholarly thinking is leading to a reinvigoration of knowledge claims derived from material things. Museums are well placed to participate in such reinvigoration. Yet, to do so they must overcome the taxonomic and systematic divisions that in the nineteenth century stimulated, but now inhibit creative thinking. The article suggests that the disciplinary ossification could be overcome and points at possible models and examples.